Analysis of the Physiological Variation in Neutrophil CD64 Expression during the Early Neonatal Period - Miyake, Fuyu; Ishii, Masahiro; Hoshina, Takayuki; Ichikawa, Shun; Araki, Shunsuke; Kinjo, Tadamune; Shibata, Eiji; Hachisuga, Toru; Kusuhara, Koichi (American Journal of Perinatology, 2016)
Background Several biomarkers for the diagnosis of sepsis are elevated during the early neonatal period due to physiological variations. The aim of this study was to investigate the physiological variation in neutrophil CD64 (nCD64) expression during the early neonatal period and the change in nCD64 expression in neonates with noninfectious diseases.Methods Of 71 neonates enrolled in this prospective study, 5 and 51 were diagnosed as having bacteremia and noninfectious diseases, respectively. Fifteen healthy neonates were enrolled as normal controls. Peripheral white blood cell counts, serum C-reactive protein and procalcitonin levels, and nCD64 expression were examined at birth and on the first and fifth day of life in neonates with noninfectious diseases and healthy neonates. In neonates with bacteremia, these markers were measured at onset.Results nCD64 expression was significantly higher in neonates with bacteremia (median, 1,992) than in those with noninfectious diseases (1,823, p < 0.001) and healthy neonates (1,848, p = 0.002). Unlike other biomarkers, no differences in nCD64 expression were observed on the same days between neonates with noninfectious diseases and healthy neonates.Conclusion nCD64 expression may be a useful marker for the diagnosis of bacterial infection in the early neonatal period, because it does not show any physiological variations.
Keywords: neutrophil CD64; early neonatal period; physiological variation; bacteremia; noninfectious diseases